Accuracy of CTA evaluations in daily clinical practice for large and medium vessel occlusion detection in suspected stroke patients. (December 2021) - Duvekot, Martijne H. C.; van Es, Adriaan C. G. M.; Venema, Esmee; Wolff, Lennard; Rozeman, Anouk D.; Moudrous, Walid; Vermeij, Frédérique H.; Lingsma, Hester F.; Bakker, Jeannette; Plaisier, Aarnout S.; Hensen, Jan-Hein J.; Lycklama à Nijeholt, Geert J.; et al.
Introduction: Early detection of large vessel occlusion (LVO) is essential to facilitate fast endovascular treatment. CT angiography (CTA) is used to detect LVO in suspected stroke patients. We aimed to assess the accuracy of CTA evaluations in daily clinical practice in a large cohort of suspected stroke patients. Patients and methods: We used data from the PRESTO study, a multicenter prospective observational cohort study that included suspected stroke patients between August 2018 and September 2019. Baseline CTAs were re-evaluated by an imaging core laboratory and compared to the local assessment. LVO was defined as an occlusion of the intracranial internal carotid artery, M1 segment, or basilar artery. Medium vessel occlusion (MeVO) was defined as an A1, A2, or M2 occlusion. We calculated the accuracy, sensitivity, and specificity to detect LVO and LVO+MeVO, using the core laboratory evaluation as reference standard. Results: We included 656 patients. The core laboratory detected 89 LVOs and 74 MeVOs in 155 patients. Local observers missed 6 LVOs (7%) and 28 MeVOs (38%), of which 23 M2 occlusions. Accuracy of LVO detection was 99% (95% CI: 98–100%), sensitivity 93% (95% CI: 86–97%), and specificity 100% (95% CI: 99–100%). Accuracy of LVO+MeVO detection was 95% (95% CI: 93–96%), sensitivity 79% (95% CI: 72–85%), and specificity 99% (95% CI: 98–100%). Discussion and Conclusion: CTA evaluations in daily clinical practice are highly accurate and LVOs are adequately recognized. The detection of MeVOs seems more challenging. The evolving EVT possibilities emphasize the need to improve CTA evaluations in the acute setting.